Long-term ureteroscopic management of upper tract urothelial carcinoma: 28-year single-centre experience. (27th July 2020) - Maruyama, Yuki; Araki, Motoo; Wada, Koichiro; Yoshinaga, Kasumi; Mitsui, Yosuke; Sadahira, Takuya; Nishimura, Shingo; Edamura, Kohei; Kobayashi, Yasuyuki; Watanabe, Masami; Watanabe, Toyohiko; Monga, Manoj; et al.
Abstract: Background: Long-term survival outcomes of patients who undergo endoscopic management of non-invasive upper tract urothelial carcinoma remain uncertain. The longest mean follow-up period in previous studies was 6.1 years. This study reports the long-term outcomes of patients with upper tract urothelial carcinoma who underwent ureteroscopic ablation at a single institution over a 28-year period. Methods: We identified all patients who underwent ureteroscopic management of upper tract urothelial carcinoma as their primary treatment at our institution between January 1991 and April 2011. Survival outcomes, including overall survival, cancer-specific survival, upper-tract recurrence-free survival and renal unit survival, were estimated using Kaplan−Meier methodology. Results: A total of 15 patients underwent endoscopic management, with a mean age at diagnosis of 66 years. All patients underwent ureteroscopy, and biopsy-confirmed pathology was obtained. Median (range; mean) follow-up was 11.7 (2.3–20.9, 11.9) years. Upper tract recurrence occurred in 87% ( n = 13) of patients. Twenty percent ( n = 3) of patients proceeded to nephroureterectomy. The estimated cancer-specific survival rate was 93% at 5, 10, 15 and 20 years. Estimated overall survival rates were 86, 80, 54 and 20% at 5, 10, 15 and 20 years. Only one patient experienced cancer-specific mortality. The estimated mean and median overall survival times were 14.5 and 16.6 years, respectively. The estimated mean cancer-specific survival time was not reached. Conclusions: Although upper tract recurrence is common, endoscopic management of non-invasive upper tract urothelial carcinoma provides a 90% cancer-specific survival rate at 20 years in selected patients. Abstract : The long-term (mean, 11.9 years) survival outcomes of selected patients who underwent endoscopic management of upper tract urothelial cell carcinoma were excellent with 90% cancer-specific survival rate at 20 years.